Ekumenisiteit in dogmatologiese perspektief - Wethmar, C. J. (Verbum et ecclesia, 1992)
Ecumenicity in doctrinal perspective In this article ecumenicity is studied from a doctrinal point of view. This requires a twofold approach: firstly an analysis of the relevant doctrine which in this case is that of the proprietates et notae ecclesiae and secondly a description of the ecumenical implications of the nature of church doctrine as such. This study indicates how the latter approach complements and enriches the former.